Use of the international systemic scleroderma activity index - Maya Nikolayevna Starovoitova; L P Ananyeva; O A Koneva; O V Desinova; N G Guseva (Современная ревматология)
Up to now, it is difficult to determine systemic scleroderma (SSD) activity because of the lack of validated tools to estimate changes in the pathological process. Attempts have been made to develop unified activity assessing methods for many years. The indices proposed by the European SSD Group are most popular today. This paper gives the results of using this index in a cohort of Russian patients.